PENGARUH ORIENTASI KEWIRAUSAHAAN, INOVASI RADIKAL, DAN STRATEGI BISNIS TERHADAP KINERJA PERUSAHAAN - Adyuta, Hafizh Rakha; Prabandari, Sri Palupi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The purpose of this study was to determine the effect of entrepreneurial orientation, radical innovation, and business strategy on company performance. The population in this study, namely handicraft SMEs in the city of Malang returned to 209, while the sample of this study was micro, small and medium enterprises engaged in handicrafts in the city of Malang. Determination of the number of samples using the Slovin formula with an allowance of 0.1 and obtained as many as 100 samples. The method used in this study is a quantitative method with Multiple Linear Regression Analysis using SPSS 25 Software. The sampling technique uses simple random sampling and gets 100 respondents who are distributed both through online and offline questionnaires. The results showed that entrepreneurial orientation, radical innovation, and business strategy had a positive and significant effect on purchasing decisions. In the research application variables, handicraft SMEs in Malang City are good, but each variable needs to be developed to get maximum performance.